2010
DOI: 10.3109/09513590.2010.507283
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oral contraceptives and metformin on anti-Müllerian hormone serum levels in women with polycystic ovary syndrome and biochemical hyperandrogenemia

Abstract: AMH serum levels were significantly decreased under treatment with 35 μg ethinylestradiol plus 2 mg cyproterone acetate, due to decrease in androgens and suppression of gonadotropins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 24 publications
5
41
1
2
Order By: Relevance
“…These associations were not seen among users of hormonal contraceptives. Controversies still exist regarding the effect of hormonal contraceptives on circulating levels of AMH (15)(16)(17)(18)(22)(23)(24). In our study on a large cohort of young women from the general population, we observed a small albeit statistically significant difference in median serum AMH of 0.4 ng/mL when comparing users and nonusers of hormonal contraceptives.…”
Section: Discussionmentioning
confidence: 52%
“…These associations were not seen among users of hormonal contraceptives. Controversies still exist regarding the effect of hormonal contraceptives on circulating levels of AMH (15)(16)(17)(18)(22)(23)(24). In our study on a large cohort of young women from the general population, we observed a small albeit statistically significant difference in median serum AMH of 0.4 ng/mL when comparing users and nonusers of hormonal contraceptives.…”
Section: Discussionmentioning
confidence: 52%
“…In this respect, various results have been reported regarding the impact of steroid suppression on serum AMH levels. Some studies reported null effect of OCP treatment on serum AMH levels [18,21,22], whereas others revealed suppressed AMH levels in normal cycling women pretreated with OCP [1,15]. In a recent case report it was demonstrated that during 16 week course of menotropin treatment both serum AMH and AFC increased in an IHH patient.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that AMH concentrations are not influenced by oral contraception, 8 but this finding has not been confirmed. 9 Contraceptives containing 35mg of ethynylestradiol and 2mg of cyproterone acetate cause a significant suppression of gonadotropins and testosterone levels, a reduction in the number of ovarian small follicles as well as a significant reduction in AMH levels. 9 On the other hand, gonadotropinreleasing hormone (GnRH) agonists do not seem to affect AMH concentrations.…”
Section: Amh: Production Levels and Actions In Womenmentioning
confidence: 99%
“…9 Contraceptives containing 35mg of ethynylestradiol and 2mg of cyproterone acetate cause a significant suppression of gonadotropins and testosterone levels, a reduction in the number of ovarian small follicles as well as a significant reduction in AMH levels. 9 On the other hand, gonadotropinreleasing hormone (GnRH) agonists do not seem to affect AMH concentrations. 10 Finally, there are no racial differences in the hormone levels between women of comparable age.…”
Section: Amh: Production Levels and Actions In Womenmentioning
confidence: 99%